2014
DOI: 10.2337/db14-0228
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin as a Potential Causal Factor in Type 2 Diabetes Risk: A Mendelian Randomization Study

Abstract: Circulating bilirubin, a natural antioxidant, is associated with decreased risk of type 2 diabetes (T2D), but the nature of the relationship remains unknown. We performed Mendelian randomization in a prospective cohort of 3,381 participants free of diabetes at baseline (age 28-75 years; women 52.6%). We used rs6742078 located in the uridine diphosphateglucuronosyltransferase locus as an instrumental variable (IV) to study a potential causal effect of serum total bilirubin level on T2D risk. T2D developed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 51 publications
6
97
2
Order By: Relevance
“…In clinical studies, high serum levels of bilirubin are negatively regulates the prevalence of various disorders including cardiovascular diseases such as 4-10 chronic kidney disease, 26 type 2 diabetes, 27 and its complications such as neuropathy 28 and nephropathy. 29 Low bilirubin is a potent endogenous antioxidant, 11 antioxidant property in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, high serum levels of bilirubin are negatively regulates the prevalence of various disorders including cardiovascular diseases such as 4-10 chronic kidney disease, 26 type 2 diabetes, 27 and its complications such as neuropathy 28 and nephropathy. 29 Low bilirubin is a potent endogenous antioxidant, 11 antioxidant property in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the causal association of eosinophil on complex traits and diseases, we performed MR analyses using eos-GRSs as instrumental variables (Abbasi et al, 2015;Prins et al, 2016) in two approaches. MR approach using individual-level data.…”
Section: Data Analysesmentioning
confidence: 99%
“…Consistent with this data, higher serum bilirubin levels were reported to protect from diabetes mellitus in the US National Health and Nutrition Examination Survey (NHANES) on almost 16,000 subjects [7]. Importantly, recent report showed that genetically elevated bilirubin levels are causally protective against the development of type 2 diabetes using Mendelian randomization in a cohort study [8].…”
mentioning
confidence: 54%